Impact of Physiotherapy on Serum CRP Level in Post-Stroke Patients: A Marker of Recovery - Bacha, Khaista; Khan, Aizaz Ullah; Hoor, Sana; Ahmad, Zahoor; Khan, Tahir (Indus Journal of Bioscience Research, 2025)
Systemic inflammation, as reflected by elevated C-reactive protein (CRP) levels, is associated with poor outcomes in stroke recovery. Physiotherapy is a cornerstone of post-stroke rehabilitation, but its effect on inflammatory biomarkers such as CRP remains underexplored. This study investigates the impact of structured physiotherapy on serum CRP levels in post-stroke patients. Methods: A prospective, interventional study was conducted at Pak-Medical Centre, Timergara. One hundred post-stroke patients were randomly assigned to either a physiotherapy group (n=50), receiving structured rehabilitation for 12 weeks, or a control group (n=50), receiving standard care. Serum CRP levels were measured at baseline, 6 weeks, and 12 weeks using high-sensitivity assays. Functional recovery was assessed using the Fugl-Meyer Assessment (FMA) and Modified Rankin Scale (mRS). Results: The physiotherapy group exhibited a significant reduction in serum CRP levels at 6 and 12 weeks (p < 0.001), along with marked improvements in FMA and mRS scores compared to the control group. A positive correlation was observed between CRP reduction and functional recovery, suggesting a potential mechanistic link. Conclusion: Structured physiotherapy significantly reduces systemic inflammation and improves motor and functional outcomes in post-stroke patients. CRP may serve as a useful biomarker for monitoring rehabilitation efficacy. These findings support the integration of physiotherapy into routine post-stroke care protocols.